2013
DOI: 10.1093/nar/gkt567
|View full text |Cite
|
Sign up to set email alerts
|

LHX2 regulates the neural differentiation of human embryonic stem cells via transcriptional modulation of PAX6 and CER1

Abstract: The LIM homeobox 2 transcription factor Lhx2 is known to control crucial aspects of neural development in various species. However, its function in human neural development is still elusive. Here, we demonstrate that LHX2 plays a critical role in human neural differentiation, using human embryonic stem cells (hESCs) as a model. In hESC-derived neural progenitors (hESC-NPs), LHX2 was found to be expressed before PAX6, and co-expressed with early neural markers. Conditional ectopic expression of LHX2 promoted ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
56
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 63 publications
2
56
1
Order By: Relevance
“…It has been suggested that NC competence segregates with the neuralized domain of the ectoderm (Pieper et al, 2012;Schlosser, 2008). We have examined the expression dynamics of a number of neural-related transcripts, including LHX2, PAX6, SOX1, SOX2, OTX2 and HES5 (Greber et al, 2011;Hou et al, 2013;Zhang et al, 2010). Variable and mild (∼10-fold or less) increases in expression were observed in only a subset of these genes (PAX6, SOX1, SOX2, OTX2) and others were not induced at all (LHX2 and HES5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that NC competence segregates with the neuralized domain of the ectoderm (Pieper et al, 2012;Schlosser, 2008). We have examined the expression dynamics of a number of neural-related transcripts, including LHX2, PAX6, SOX1, SOX2, OTX2 and HES5 (Greber et al, 2011;Hou et al, 2013;Zhang et al, 2010). Variable and mild (∼10-fold or less) increases in expression were observed in only a subset of these genes (PAX6, SOX1, SOX2, OTX2) and others were not induced at all (LHX2 and HES5).…”
Section: Discussionmentioning
confidence: 99%
“…The neural induction program in human embryos and ESCs has been studied (Greber et al, 2011;Hou et al, 2013;Zhang et al, 2010). Although there was transient and variable upregulation of the pluripotency/neural markers SOX2, SOX1 and OTX2 during our NC cell induction, other pre-neural and mature neural progenitor markers, such as LHX2 and HES5, were never induced (data not shown; Fig.…”
Section: Human Neural Crest Induction Requires An Early and Balanced mentioning
confidence: 95%
“…Mediated through its DNA-binding homeodomain, Lhx2 controls hundreds of downstream genes directly (34,35). We next aimed to identify molecules that are relevant to cortical area patterning and, mediated by its protein-binding LIM domain (36), interact biochemically with Lhx2.…”
Section: Significancementioning
confidence: 99%
“…20 Hou et al demonstrated that Lhx2 binds to enhancers rather than the promoter of PAX6 to induce neural differentiation from human embryonic stem cells. 21 Also, the LIM domain of Lhx2 functions as a coactivator through interaction with MRG1, leading to recruitment of p300/CBP to stimulate glycoprotein hormone a-subunit gene expression. 22 On the other hand, Lhx2 negatively regulates the PRL promoter in pituitary cell lines by an as yet unknown mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Lhx2 activates antagonists of WNT and BMP protein in certain areas to inhibit these signaling pathways in the developing forebrain. 21,24 Because WNT and BMP signaling are involved in osteoblast differentiation and bone formation, we examined whether Lhx2 directly affects osteoblast differentiation and function. 25 Overexpression of Lhx2 in osteoblasts showed a marginal effect on BMP2-mediated osteoblast differentiation and nodule formation (Figures 2c and d).…”
Section: Discussionmentioning
confidence: 99%